Pete the cat saves up - Dean, Kim, 1969-; Dean, James, 1957- (Pete the cat., 2023)
"Pete the Cat wants a supercool Sharkbot toy, but he doesn't have enough money in his piggy bank. He takes on odd jobs -- from shoveling snow to selling lemonade and more -- and saves every penny. How long will it take for him to earn enough money to buy the toy? Early readers will love saving up with Pete!" --